(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The present study assessed the changes in socio-economic conditions of small scale broiler farmers in rural areas of Bangladesh. The population comprised the small scale broiler farmers who reared at least 300 to less than 2000 birds in the rural areas of Sadar Upazila of Mymensingh district, among which a total of 50 samples were randomly selected for the study. The necessary data on different socio-economic parameters were collected from the respondents through personal interview with the pre-tested interview schedule. Findings showed that annual employment opportunities for unemployed family members of broiler farmers were 302.96 man-days. The overall income and expenditure of the farmers were increased by TK.6100 and TK.3064.66 after involving in broiler farming. Cash in hand and savings with bank raised by 142.71% and 201.63% respectively. Drinking water from own tube-well increased by 135.71% and katcha latrines decreased by 76.47%. Consumption of meat, egg, and fruits per month per household were increased by 94.32%, 34.53% and 56.14% respectively in post farming situation. The number of school going children, household assets and health status also improved. So, small scale broiler farming has positive and significant impact for the development of socio-economic status of the farmers as well as the improvement of rural livelihood. Keywords: Broiler farming; Rural livelihood; Socio-economic development DOI: 10.3329/jbau.v7i2.4752 J. Bangladesh Agril. Univ. 7(2): 395-402, 2009